Does the stock of money have any causal significance? - Philip Arestis; Malcolm Sawyer (Levy Economics Institute of Bard College, 2002)
Recent developments in macroeconomics, and in economic policy in general, have produced a new consensus economy-wide model, in which the stock of money does not play any causal role, but operates as a mere residual in the economic process. The absence of the stock of money in many current debates over monetary policy has prompted the deputy governor of the Bank of England to note the irony of the situation: as central banks became more and more concerned with price stability, less and less attention is paid to money. Indeed in several countries, the decline of interest in money appears to have coincided with low inflation. In turn, a number of contributions have attempted, wittingly or unwittingly, to reinstate a more substantial role for money in this new macroeconomics. In this paper we argue that these attempts to reinstate money in current macroeconomic thinking entail two important problems. First, they contradict an important theoretical property of the new consensus macroeconomic model, namely, that of dichotomy between the monetary and the real sector. Second, some of these attempts either fail in terms of their objective or merely reintroduce the problem rather than solve it. We conclude that if money is to be given a causal role in the new consensus model, more substantial research is needed.
Keywords: 330